Influence of sildenafil and tadalafil on the enzyme- and transporter-inducing effects of bosentan and ambrisentan in LS180 cells - Weiß, Johanna; Theile, Dirk; Burhenne, Jürgen; Riedel, Klaus-Dieter; Haefeli, Walter E. (Biochemical pharmacology, 2013)
The combinations of the endothelin-1 receptor antagonists bosentan or ambrisentan with the phosphodiesterase 5 inhibitors sildenafil or tadalafil are current standard therapies of advanced pulmonary arterial hypertension. However, these drugs have a number of drug interactions. Changes of bosentan pharmacokinetics by sildenafil are attributed to reduced hepatic uptake as a consequence of inhibition of organic anion transporting polypeptides. We therefore tested in vitro the hypothesis that sildenafil and tadalafil reduce the enzyme- and transporter-inducing effects of bosentan or ambrisentan by preventing cellular access. Although intracellular concentrations of bosentan and ambrisentan (measured by high pressure liquid chromatography coupled with tandem mass-spectrometry) after four days of incubation of LS180 cells were lower when sildenafil or tadalafil were present, quantification of mRNA expression in these cells by real-time reverse transcription polymerase chain reaction revealed that bosentan and ambrisentan-mediated induction was stable or even increased in combination with sildenafil or tadalafil. For the drug transporter P-glycoprotein this was confirmed at the protein and functional level with highly significant correlations between P-gp mRNA, protein, and function. Moreover, using a reporter gene assay in LS180 cells, our study demonstrates for the first time that tadalafil is a potent, ambrisentan a weak, and sildenafil no activator of pregnane X receptor. In conclusion, our study demonstrates that although sildenafil and tadalafil indeed reduce intracellular concentrations of bosentan and ambrisentan in LS180 cells, they do not mitigate the inducing effects of these endothelin-1 receptor antagonists.
Available online 5 December 2012
Gesehen am 09.05.2019